Ureteritis Cystica Presenting with Atrophic Kidney: Report of a Case - Ayca Tan; Saime Unluoglu; Umit Bayol; Sehnaz Emil Sayhan; Deniz Altinel (The Scientific World Journal)
Ureteritis cystica is a rare proliferative condition that is found predominantly in the bladder, renal pelvis, and upper ureter. It may occlude the ureteral lumen and should be considered in the reasons for an atrophic kidney. A 65-year-old-female with a 2-year history of right flank pain that increased in the last 2 months was presented. Abdominal ultrasonography revealed right-sided atrophic kidney. Nephroureterectomy was performed. On the gross examination, along the ureter wall, there were numerous polyps, 0.5 cm in maximum diameter, protruding into the lumen. On the histopathological evaluation, ureteritis cystica and chronic pyelonephritis was detected. In conclusion, ureteritis cystica is a benign and indolent lesion that needs to be kept in mind among the causes of renal atrophy.